RD Sharma - Mathematics

Book: RD Sharma - Mathematics

Chapter: 7. Values of Trigonometric Functions at Sum of Difference of Angles

Subject: Maths - Class 11th

Q. No. 19 of MCQ

Listen NCERT Audio Books to boost your productivity and retention power by 2X.


Mark the correct alternative in the following:

If A – B = π /4, then (1 + tan A) (1 – tanB) is equal to

1+tan A tan B=tan A-tan B

tan A-tan B-tan A tan B=1

add both side 1

1+tan A-tan B-tan A tan B=1+1

(1+tan A)(1+tan B)=2


put A=0 AND

(1+tan A )(1-tan A )=1× 2

Chapter Exercises

More Exercise Questions